Adherence to a Long-Term Physical Activity and Exercise Program After Stroke Applied in a Randomized Controlled Trial. Issue 1 (17th October 2018) - Gunnes, Mari; Langhammer, Birgitta; Aamot, Inger-Lise; Lydersen, Stian; Ihle-Hansen, Hege; Indredavik, Bent; Reneflot, Kristine H; Schroeter, Walburga; Askim, Torunn; ,
Abstract: Background: Persistent physical activity is important to maintain motor function across all stages after stroke. Objective: The objective of this study was to investigate adherence to an 18-month physical activity and exercise program. Design: The design was a prospective, longitudinal study including participants who had had a stroke randomly allocated to the intervention arm of a randomized controlled trial. Methods: The intervention consisted of individualized monthly coaching by a physical therapist who motivated participants to adhere to 30 minutes of daily physical activity and 45 minutes of weekly exercise over an 18-month period. The primary outcome was the combination of participants' self-reported training diaries and adherence, as reported by the physical therapists. Mixed-effect models were used to analyze change in adherence over time. Intensity levels, measured by the Borg scale, were a secondary outcome. Results: In total, 186 informed, consenting participants who had had mild-to-moderate stroke were included 3 months after stroke onset. Mean age was 71.7 years (SD = 11.9). Thirty-four (18.3%) participants withdrew and 9 (4.8%) died during follow-up. Adherence to physical activity and exercise each month ranged from 51.2% to 73.1%, and from 63.5% to 79.7%, respectively. Adherence to physical activity increased by 2.6% per month (odds ratio = 1.026, 95% CI = 1.014–1.037). Most of the exercise was performed at moderate-to-high intensity levels, ranging from scores of 12 to 16 on the Borg scale, with an increase of 0.018 points each month (95% CI = 0.011–0.024). Limitations: Limitations included missing information about adherence for participants with missing data and reasons for dropout. Conclusions: Participants with mild and moderate impairments after stroke who received individualized regular coaching established and maintained moderate-to-good adherence to daily physical activity and weekly exercise over time.